Supply and demand analysis of mangosteen in Mindanao - Juanillo, Karla Joanna D.
The supply and demand situation of mangosteen in MIndanao was analyzed by conducting an industry analysis, identifying the factors affecting the supply and demand of mangosteen as well as calculating price, income and cross-price elasticities. A 20-year time series data fro 1990 o 2009, which was taken from each region of Mindanao, was used to generate the regression models. The supply and demand of mangosteen were also estimated using Ordinary Least Squares (OLS) through the Gretl software. Results of the study revealed that variability in the quantity supplied is explained by the independent variable price (own price) of mangosteen and the price of fertilizer, which conforms to economic theory. Hence, as price of mangosteen increases it is expected that quantity supply will also increase. Moreover, the responsiveness of price to the supply for mangosteen is inelastic which implies that changes in the price of mangosteen have a little influence on the quantity supplied for fresh mangosteen. Alternatively, fertilizer price (input cost) carries a negative coefficient which implies that the industry must not rely on fertilizer alone to increase the production of mangosteen but to find alternative ways to increase its productive capacity through the application of technology with the aid of responsible government agencies. It was also found out that area is not a significant variable in the supply model of mangosteen because of the lag effect of area planted/harvested to the volume of production. On the hand, demand for mangosteen is affected by the per capita income. However, its negative income coefficient does not conform to the assumed relationship to the quantity demanded. Moreover, the computed income elasticity suggests that there is significant decline in the quantity demanded for fresh mangosteen as income increases indicating that fresh mangosteen is an inferior good. The demand model apparently showed that price is not a statistically significant factor. Hence, the result for price elasticity of demand is inconclusive. With the advent growth of the demand of the food supplement sector, both in the local and international market, the proponent recommends that further studies about the supply and demand for manufactured mangosteen products be conducted. Furthermore, a market potential analysis for fresh mangosteen may also be conducted to determine its viability in the Luzon and Vizayas regions.